A 'Twitter' Generation Perspective on Biorefining. (November 2013) - Tolbert, Allison; Ragauskas, Alyse M.E.; Akinosho, Hannah; Hu, Fan; Wells, Tyrone; Sun, Qining; Meng, Xianzhi; Ragauskas, Art J.
<x xml:space="preserve">Abstract</x> A quick examination of today's biorefining leaders in government, academia and industry brings to mind a group of experts in the prime of their life. Nonetheless, the field has attracted numerous students globally which will become the generation that converts the vision to an established industry. To reflect their interests, I asked several graduate/undergraduate students involved in the field to provide "Twitter‐like" definitions of the "A, B, C" of biorefining, which have been summarized below: